Índice de morosidad en la cartera de créditos de la Fundación Espoir en la ciudad de Babahoyo, periodo 2023. - Guananga Rodríguez, Melany Alexandra (2024)
The purpose of the following investigative work is to analyze the different factors that influence the delinquency rate of the loan portfolio of the Espoir Foundation in the city of Babahoyo, period 2023, it allows us to recognize the factors by which the portfolio was increased defeated. It was founded on February 6, 1992. Its mission is to promote the economic, social and health development of microentrepreneurs in Ecuador and its vision is to be specialized in Microfinance, with national coverage, which promotes the development and improvement of business conditions. life of Ecuadorian microentrepreneurs. For this reason we believe that through our analysis and project we can better understand why there is a high rate of delinquency that occurs in the period 2023, we seek information through techniques and instruments to obtain information and at the same time analyze the factors that are affecting the Espoir Foundation the most